Os princípios do sofrimento humano em freud e schopenhauer - Rocha Filho, Paulo de Tarso (2015)
This study to highlight the human being suffering principles, starting with the notions of instinct proposed by Sigmund Freud and the will power metaphysics of living by Schopenhauer. The hypothesis and justification for suffering is an irrevocable condition of human beings, beginning coincidentally within the being. The path chosen by this entrepreneur goes through Freud s embrionic concepts of the game of powers, found in psychic which retains, above all, the sexual impulses, getting close to those by Schopenhauer s elaborations. It brings into light both authors works, making it possible to compare them equally and a final parallel which focuses particular strategies to ignore suffering, coming from both Freud s reflections and Schopenhauer s wisdom of life plus the metaphysics of consolation.